PS 05-80 ONE-POINT LOCAL ARTERIAL STIFFNESS IN SUBJECTS WITH CHRONIC SPINAL CORD INJURY AND NO OVERT CARDIOVASCULAR DISEASE. (September 2016) - Vriz, Olga; Favretto, Serena; Bizzarini, Emiliana; Ius, Arianna; Minisini, Rosalba; Pirisi, Mario; Bossone, Eduardo
Abstract : Objective: Cardiovascular disease (CVD) is an important cause of morbidity and mortality in subjects with long-term spinal cord injury (SCI) therefore CVD prevention is crucial in this population. Clinical studies demonstrate that parameters of local arterial stiffness can predict cardiovascular events. The aim of this study was to evaluate carotid stiffness in the SCI individuals compared to able-bodied persons (ABPs). Design and Method: We recruited 145 subjects, 57 with SCI (49 M and 8 F) and 88 age and sex-matched ABPs (77 M and 11 F), mean age 42.8+/−12.8 and 45 +/−13.3 years respectively (p = 0.3). Antropometric, office blood pressure (BP) measurements and transthoracic echocardiography (TTE) were performed. One-point local arterial stiffness [(? stiffness, pressure-strain elasticity modulus (EP), arterial compliance (AC), local pulse wave velocity (PWV)] was evaluated at the level of the left common carotid artery (CCA) 1 to 2 cm before its bifurcation using a high-definition echo-tracking ultrasound (Hitachi Aloka Inc). Stiffness indices were derived from measurement of arterial diameters and brachial artery pressure. Results: In subjects with SCI, despite statistically lower body mass index (BMI) and diastolic BP compared with able-bodied persons, after adjusting for age, sex, BMI and physical activity, we found significantly higher stiffness values (and lower AC) in SCI subjects (p < 0.05). Differences remained statistically significant after adjustment for heart rate. Moreover, TTE demonstrated increased wall thickness, lower E wave, E/A ratio and early diastolic myocardial relaxation velocity on Tissue Doppler Imaging (TDI) (p < 0.05) and lower (21.8+/−4.1 vs 25.7+/−5.0, p = 0.0001). Conclusions: Subjects with post-traumatic chronic SCI and no overt cardiovascular risk factors, exhibit significantly higher CCA stiffness and initial left ventricular remodeling (as assessed by TTE) compared with ABPs. Lifestyle modifications, including regular physical exercise and weight control, should be implemented in all subjects with SCI, even at a very early stage, in order to reduce cardiovascular risk and prevent CVD.